m-kreuzer/MOM5: Version as used in Kreuzer et al., Geoscientific Model Development publication (doi 10.5194/gmd-14-3697-2021) - Leslie, Tim; Ward, Marshall; Hannah, Nic; Hoover, Nicholas; Heerdegen, Aidan; Griffies, Stephen; Kiss, Andrew; Russfiedler; Holmes, Ryan; Hailin Yan; Farneti, Riccardo; Leopardi, Paul; et al. (Zenodo, 2020)
This is a MOM5 code release as used in the Geoscientifc Model Development publication "Coupling framework (1.0) for the PISM (1.1.4) ice sheet model and the MOM5 (5.1.0) ocean model via the PICO ice shelf cavity model in an Antarctic domain" by Moritz Kreuzer, Ronja Reese, Willem Huiskamp, Stefan Petri, Torsten Albrecht, Georg Feulner and Ricarda Winkelmann.